Manʼyōshū, book 15 = [Manʼyōshū] : a new English translation containing the original text, kana transliteration, romanization, glossing and commentary - Vovin, Alexander (Global Oriental, 2009)
The largest Japanese poetic anthology, thus the most important compendium of Japanese culture of the Asuka and Nara periods, is very much more than a work of literature. The author presents the Man'yoshu preserving as far as possible the flavour, sounds and semantics of the original poems. The result is a more literate but true translation.